Pengaruh Pendidikan Kesehatan Seksualitas terhadap Sexual Self Efficacy for Female (SSEF) pada Calon Pengantin - Riski Wulan Guritno; Mawardika, Tina (Universitas Ngudi Waluyo, 2024)
Sexual Self Efficacy for Females (SSEF) is a sexual predictor, it can also be interpreted as a person’s belief in the potential quality of having sexual relations. Insufficient or low knowledge about sexuality can influence a woman’s failure or lack of confidence in sexual self-efficacy for Female (SSEF). The aim of this research is to determine the influence of providing health education about sexuality on sexual self-efficacy for Female in prospective brides and grooms in KUA Bawen District. This research uses quantitative Nonequivalent with control group design. The population of this study was all 34 prospective brides who had registered in January who were divided into a control group and an intervention group. This research sample used Total Sampling using Mann Whitney analysis. Obtained a value of p(Value) (0.01) < α (0.05). This means that there is an influence of sexual health education on the sexual self-efficacy for females (SSEF) of prospective brides in KUA Kecamatan Bawen . The results of this research can add information for prospective brides in preparation for marriage to face Sexual Self-Efficacy for Females (SSEF) through Sexuality Health Education. ABSTRAK Pengetahuan tentang seksualitas dapat mempengaruhi kegagalan atau ketidak yakinan seorang wanita tentang sexual self efficacy for female. Tujuan penelitian adalah Mengetahui adanya Pengaruh Pemberian Pendidikan Kesehatan Tentang Seksualitas Terhadap Seksual Self Effecasy For Female Pada Calon Pengantin Wanita di KUA Kecamatan Bawen. Penelitian ini menggunakan kuantitatif berbentuk Nonequivalent with control group design with control group desain. Populasi penelitian ini adalah seluruh Calon Pengantin Wanita yang telah mendaftar dibulan Januari berjumlah 34 yang dibagi menjadi kelompok kontrol dan kelompok intrvensi. Sempel penelitian ini mengunakan Total Sampling dengan menggunakan analisa Mann Whitney. Diperoleh nilai p(Value) (0,01) < α (0,05) Artinya Ada Pengaruh Pendidikan Kesehatan Seksualitas Terhadap Seksual Self Efficacy For Female (SSEF) Calon Pengantin Wanita di KUA Kecamatan Bawen.Hasil penelitian ini dapat menambah informasi bagi Calon Pengantin Wanita dalam persiapan pernikahan untuk menghadapi Seksual Self Efficacy For Female (SSEF) melalui Pedidikan Kesehatan Seksualitas.